2021
DOI: 10.1134/s0003683821100124
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Novel Naphthoquinone Derivatives in the Commonly-used Chassis Cells Saccharomyces cerevisiae and Escherichia coli

Abstract: Naphthoquinones harboring 1,4-naphthoquinone pharmacophore are considered as privileged structures in medicinal chemistry. In pharmaceutical industry and fundamental research, polyketide naphthoquinones were widely produced by heterologous expression of polyketide synthases in microbial chassis cells, such as Saccharomyces cerevisiae and Escherichia coli . Nevertheless, these cell factories still remain, to a great degree, black boxes that often exceed engineers’ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…With the molecular docking scores of less than −7 kcal/mol, ADRP and its ligands revealed that all the carotenoids had strong binding affinities toward ADRP (W. Wu et al, 2021 ). Particularly, alpha‐carotene, capsanthin, and neoxanthin showed the lowest binding energies of −9.6, 9.4, and − 9.4 kcal/mol, respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the molecular docking scores of less than −7 kcal/mol, ADRP and its ligands revealed that all the carotenoids had strong binding affinities toward ADRP (W. Wu et al, 2021 ). Particularly, alpha‐carotene, capsanthin, and neoxanthin showed the lowest binding energies of −9.6, 9.4, and − 9.4 kcal/mol, respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%